1993
DOI: 10.1007/bf01352206
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting properties of YBa2Cu3O7-Au composites

Abstract: By X-ray diffraction and photoelectron spectroscopy, we have demonstrated that Au is incorporated in the YBCO lattice up to a concentration 0.1. An XPS study gave evidence for an electronic valence state Au 1 +. Its replacement in the Cu(1 ) site appears questionable due to the large difference in ionic radii (Cu2+: 0.073 nm; Au 1+: 0.1 37 nm). The so called 'irreversibility lines' determined by AC susceptibility measurements are strongly affected by the doping. Up to the limit of solubility in the grains, an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Figure 2 shows the zero-field-cooled (ZFC) and the field-cooled (FC) magnetization versus temperature characteristic curves of Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d for various Au mole fractions x = 0, 0.15, 0.1, 0.15, and 0.2. The critical temperatures of the superconductivity transitions for Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d are independent of the Au mole fraction, and the value of the T c is approximately 92 K. This behavior is in reasonable agreement with the results reported by Huong et al [16]. However, second transitions appear between 65 and 80 K and result from mixed phases being created in the Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d superconductors as the Au mole fraction increases.…”
Section: Resultssupporting
confidence: 82%
“…Figure 2 shows the zero-field-cooled (ZFC) and the field-cooled (FC) magnetization versus temperature characteristic curves of Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d for various Au mole fractions x = 0, 0.15, 0.1, 0.15, and 0.2. The critical temperatures of the superconductivity transitions for Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d are independent of the Au mole fraction, and the value of the T c is approximately 92 K. This behavior is in reasonable agreement with the results reported by Huong et al [16]. However, second transitions appear between 65 and 80 K and result from mixed phases being created in the Y 1 Ba 2 Cu 3± ±3x Au 3x O 7± ±d superconductors as the Au mole fraction increases.…”
Section: Resultssupporting
confidence: 82%
“…Furthermore, it has been shown that Au has a certain solubility in YBCO so one could expect an efficient incorporation of gold atoms [35]. However, an incorporation of gold atoms should lead to an enhancement of the c-axis rather than to a thickness reduction as observed by the authors [36]. Furthermore, Rutherford backscattering spectrometry measurements proved that no gold atoms can be found at interstitial places.…”
Section: Sem and White-light Interferometry Resultsmentioning
confidence: 82%
“…Although this reduction of the c-axis in the gold modified sample parts is quite small, it is consistent over all the investigated samples. We do not expect a possible incorporation of gold atoms in the YBCO crystal structure to be responsible for this effect because it would only lead to an increase of the c-axis [13]. Instead we propose that a slight increase of the oxygen content might be causing the observed reduction of the YBCO c-axis [25].…”
Section: Superconducting Properties Of Au Modified Ybcomentioning
confidence: 82%
“…The interplay of Au and YBCO has often been studied. In contrast to the existing work, which often was based on the usage of Au/YBCO composite targets [12] or grounded and sintered bulk pellets [13], we employ a self-organisation technique out of a gold seed layer. Thin gold layers with thicknesses between 1 and 10 nm were deposited on polished SrTiO 3 (100) single crystal substrates prior to the YBCO deposition using DC-sputtering (p 0 < 5 × 10 −4 Pa).…”
Section: Sample Preparationmentioning
confidence: 99%